The Utilization of Bottom Ash Coal for Briquette Products by Adding Teak Leaves Charcoal, Coconut Shell Charcoal, and Rice Husk Charcoal - Syafrudin Syafrudin; Badrus Zaman; Indriyani Indriyani; A. Stevie Erga; H. Bunga Natalia (Diponegoro University, 2015)
The limitations of the availability of energy sources especially fuel oil has become a serious threat for the society. The use of coal for energy source as the replacement of fuel oil, in one hand, is very profitable, but on the other hand, will cause problem which is the coal ash residue. This coal ash is a by-product of coal combustion. This coal ash contains bottom ash. Through this observation, the bottom ash can be processed to be charcoal if added by teak leaves, coconut shell, and rice husk. Also, this observation needs to add binder materials for further processing in order to form briquette. It can be used as alternative fuel, the utilization of bottom ash and biomass will give positive impact to the environment. This observation was conducted by using compositions such as bottom ash, teak leaves, coconut shell, and rice husk. The treatment was using comparison 100%:0% ; 80%:20% ; 60%:40% ; 50%:50% ; 40%:60% ; 20%:80% ; 0%:100%. The result that the best briquette was on the composition of 20% bottom ash : 80% coconut shell. The characteristic values from that composition were moisture content of 3.45%, ash content of 17,32%, calorific value of 7.945,72 Cal/gr, compressive strength of 2,18 kg/cm2, level of CO of 105 mg/m3, and heavy metals Cu of 29,83 µg/g and Zn 32,99 µg/g. The characteristic value from each briquette composition treatment showed that the increasing usage proportion of biomass as added material for briquette was able to increase its moisture content and calorific value. Besides, it is also able to decrease its ash content and compressive strength